Solid-state evaluation and polymorphic quantification of venlafaxine hydrochloride raw materials using the Rietveld method - Bernardi, Larissa S. (2013)
Venlafaxine hydrochloride (VEN) is an antidepressant drug widely used for the treatment of depression. The purpose of this study was to carry out the preparation and solid state characterization of the pure polymorphs (Forms 1 and 2) and the polymorphic identification and quantification of four commercially-available VEN raw materials. These two polymorphic forms were obtained from different crystallization methods and characterized by X-ray Powder Diffraction (XRPD), Diffuse Reflectance Infrared Fourier Transform (DRIFT), Raman Spectroscopy (RS), liquid and solid state Nuclear Magnetic Resonance (NMR and ssNMR) spectroscopies, Differential Scanning Calorimetry (DSC), and Scanning Electron Microscopy (SEM) techniques. The main differences were observed by DSC and XRPD and the latter was chosen as the standard technique for the identification and quantification studies in combination with the Rietveld method for the commercial raw materials (VEN1–VEN4) acquired from different manufacturers. Additionally Form 1 and Form 2 can be clearly distinguished from their 13C ssNMR spectra. Through the analysis, it was possible to conclude that VEN1 and VEN2 were composed only of Form 1, while VEN3 and VEN4 were a mixture of Forms 1 and 2. Additionally, the Rietveld refinement was successfully applied to quantify the polymorphic ratio for VEN3 and VEN4.